Socialism in Cuba. 65 years of resilient realities - HERNÁNDEZ RODRÍGUEZ, Octavio (Utopía y Praxis Latinoamericana, 2025)
In Cuba, the socialist system is 65 years old. A political system that differs from most Latin American democratic countries. Thus, it seems that Cuba is a latent and courageous anachronism against the U.S. blockade. The objective of this essay is to describe a complex reality of Cuban society in which conflicting positions and different visions are mixed. For this, a qualitative methodology was used with a participant observation technique through a stay on the island for 10 days in June 2024, in which the life of Cuban society was observed and participated. The results suggest that Cubans emigrate and return and it may be due to factors such as a part of the population that benefits most from the situation and the economic policy and the day-to-day life of Cubans, which is a complex and difficult reality overcome with skills to survive.and economic policy.